Impacts of intensive aquaculture on hydrological systems and water quality parameters in the Keban Strait (Elazığ-Malatya) - Aydin, Murat (Ege Univ, Fac Fisheries, 2025)
This study geographically evaluates the pressure on land use and water resources, which is increasing due to global factors such as climate change, population growth, and intense urbanization. The sustainability of limited freshwater resources has been analyzed, particularly through the example of the Keban Strait. In this area located between the provinces of Elaz & imath;& gbreve; and Malatya, the effects of aquaculture activities that developed after the Keban and Karakaya dams on water quality have been examined. Using a mixed research method, water samples taken from three sampling points were evaluated in terms of physical and chemical parameters; water quality deteriorated overtime. This study provides original micro-level data on water resource management and sustainability, emphasizing the need for similar research in other arid regions of T & uuml;rkiye.
Keywords: Geography; water management; sustainability; aquaculture; Keban strait; Elaz & imath;& gbreve;